PREVALENSI GIZI LEBIH DAN OBESITAS PENDUDUK DEWASA DI INDONESIA - Sandjaja Sandjaja; Sudikno Sudikno (GIZI INDONESIA, 2005)
There is a trend that the prevalence of overweight and obesity is increasing in Indonesia in the last decade. Overweight and obesity has been shown to increase risk of several degenerative diseases. Using data from household health survey (SKRT), data analysis of 20.137 adults was done, comprised of 9.390 men and 10.747 women from urban and rural areas. Overweight and obesity was defined for body mass index (BMI) 25.0 – 27.0, while obesity was defined for BMI 27.0. The study found that the prevalence of overweight was 7.2% among men and 10.4% among women. The prevalence of overweight was higher in urban areas (10.8%) than in rural areas (7.5%). The prevalence of obesity among women was more than twice (13.3%) than among men (5.3%), higher in urban areas (12.8%) than rural areas (7.1%). The peak of overweight and obesity was found at the age range of 45 – 49 years old. In conclusion, the prevalence of overweight and obesity was higher in both aspects, among women than men and in urban areas than in rural areas. The higher prevalence was found at the age of 45-49 years old.